2013
DOI: 10.1590/s1516-31802013000100020
|View full text |Cite
|
Sign up to set email alerts
|

Carotid intima-media thickness in spondyloarthritis patients

Abstract: CONTEXT AND OBJECTIVE: Accelerated atherosclerosis has become a major problem in rheumatic inflammatory disease. RESULTADOS: A ECIM média em pacientes com ES foi de 0,72 ± 0,21 mm, enquanto nos controles foi de 0,57 ± 0,13 mm (P = 0,0007). Não se encontrou associação com VHS, PCR, BASDAI e dados clínicos. Em análise univariada, maior ECIM foi encontrado nos indivíduos com maior duração de doença (P = 0,014; R Pearson = 0,40; 95% intervalo de confiança, IC = 0,06 to 0,65), aumento nos triglicerídeos (P = 0,02; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

10
11
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 29 publications
(21 reference statements)
10
11
2
Order By: Relevance
“…Increase in CIMT was not found to be associated with HLA B-27 positivity in our study, the same as in other studies [13, 15]. …”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Increase in CIMT was not found to be associated with HLA B-27 positivity in our study, the same as in other studies [13, 15]. …”
Section: Discussionsupporting
confidence: 92%
“…Also we observed a statistically significant difference in CIMT while studying a much younger population (mean age 29.43 ± 9.00 years), as compared to Cece et al [12] (36.8 ± 9.8), Hamdi et al [13] (36 ± 11), Skare et al [15] (42.89 ± 11.70), Peters et al [17] (39), and Mathieu et al [22] (40).…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…However, this could be influenced by the small number of study participants (20 AS patients and 20 healthy controls) [19]. The studies involving patients with a BASDAI > 4 demonstrated that patients with AS had a higher CIMT than those of the control group [20][21][22]. A recent study by Berg et al examining the association between disease activity in AS and mark-ers of vascular pathology concluded that the patients with high AS disease activity had a higher cardiovascular disease risk.…”
Section: Discussionmentioning
confidence: 99%
“…14 However, there appears to be no clear data in terms of atherosclerosis development related to EFT. 12,15 Accordingly, in this study, we aimed to determine the relationship between atrial EMD, CIMT, and EFT in AS, which has a complicated inflammatory nature.…”
mentioning
confidence: 99%